PENGEMBANGAN POSTER INTERAKTIF SEBAGAI MEDIA PROMOSI KESEHATAN MENGENAI 5 PILAR DIABETES MELITUS PADA PESERTA PROLANIS - Qonita Nur Tsania; Tati Ruhmawati (Politeknik Kesehatan Kemenkes Bandung, 2025)
Background: Diabetes mellitus is one of the diseases with a high prevalence in the community and has the potential to cause serious complications if not properly managed. In 2023, West Java recorded 645,390 cases, with Bandung Regency as the second-highest contributor (59,205 cases). In Margahayu Selatan Public Health Center’s area, there were 1,312 cases. A preliminary study showed most Prolanis participants had never received education on the 5 Pillars of Diabetes Mellitus. Therefore, appropriate educational media such as interactive posters are needed for health promotion. Objective: To develop interactive poster media on the 5 Pillars of Diabetes Mellitus for Prolanis participants as an educational tool for diabetes management. Methods: This study used the 4D development model (Define, Design, Development, Disseminate) and was conducted at Margahayu Selatan Public Health Center in April–May 2025. The population included all Prolanis participants, with a total sample of 53 people selected using total sampling. Media effectiveness was tested using a one-group pretest-posttest design without a control group. Results: The Define stage revealed the need for printed and interactive educational media. The Design stage produced an interactive poster containing 5 Pillars material. At the Development stage, the media was rated highly feasible: 92.5% by material experts, 100% by media experts, and 96.9% by participants. Knowledge scores increased from 77.42 to 96.96, with a p-value of 0.000 (Wilcoxon test). Conclusion: Interactive poster media is effective in increasing knowledge of Prolanis participants regarding diabetes management.